Hydroxytyrosol and Potential Uses in Cardiovascular Diseases, Cancer, and AIDS - Vilaplana-Pérez, Cristina; Auñón, David; García-Flores, Libia A.; Gil-Izquierdo, Angel (Frontiers in Nutrition, 2014)
Hydroxytyrosol is one of the main phenolic components of olive oil. It is present in the fruit and leaf of the olive (Olea europaea L.). During the past decades, it has been well documented that this phenolic compound has health benefits and a protective action has been found in preclinical studies against several diseases. Here we review its bioavailability in humans and several assays showing significant results related with cardiovascular diseases, cancer and acquired immunodeficiency syndrome (AIDS). Mechanisms of action include potent antioxidant and anti-inflammatory effects, among others. The importance of hydroxytyrosol in protection of low density lipoproteins (LDL) and consequently its implication in the reduction of cardiovascular disease risk has been highlighted by the European Food Safety Authority (EFSA), concluding that 5 mg of hydroxytyrosol and its derivatives should be consumed daily to reach this effect at physiological level. We discuss the potential uses of this compound in supplements, nutraceutic foods or topical formulations in the disease risk reduction. Finally, we conclude that more studies are needed to sustain or reject many other health claims not yet fully documented and to validate these newly available hydroxytyrosol-based products, because it seems to be a good candidate to reduce the risk of diseases mentioned.